Cecropin A: investigation of a host defense peptide with multifaceted immunomodulatory activity in a chicken hepatic cell culture - Márton, Rege Anna; Sebők, Csilla; Mackei, Máté; Tráj, Patrik; Vörösházi, Júlia; Kemény, Ágnes; Neogrády, Zsuzsanna; Mátis, Gábor (Frontiers in Veterinary Science, 2024)
Host defense peptides (HDPs) are increasingly referred to as promising candidates for the reduction of the use of conventional antibiotics, thereby combating antibiotic resistance. As HDPs have been described to exert various immunomodulatory effects, cecropin A (CecA) appears to be a potent agent to influence the host inflammatory response. In the present study, a chicken primary hepatocyte-nonparenchymal cell co-culture was used to investigate the putative immunomodulatory effects of CecA alone and in inflammatory conditions evoked by polyinosinic-polycytidylic acid (Poly I:C). To investigate the viability of the cells, the extracellular lactate dehydrogenase (LDH) activity was determined by colorimetric assay. Inflammatory markers interleukin (IL)-8 and transforming growth factor-ß1 (TGF-ß1) were investigated using the ELISA method, whereas concentrations of IL-6, IL-10, and interferon-γ (IFN-γ) were assayed by Luminex xMAP technology. Extracellular H2O2 and malondialdehyde levels were measured by fluorometric and colorimetric methods, respectively. Results of the lower concentrations suggested the safe application of CecA, however, it might contribute to hepatic cell membrane damage at its higher concentrations. We also found that the peptide alleviated the inflammatory response, reflected by the decreased production of the pro-inflammatory IL-6, IL-8, and IFN-γ. In addition, CecA diminished the levels of anti-inflammatory IL-10 and TGF-ß1. The oxidative markers measured remained unchanged in most cases of CecA exposure. In summary, CecA displayed a multifaceted immunomodulatory but not purely anti-inflammatory activity on the hepatic cells and might be suggested to maintain the hepatic inflammatory homeostasis in Poly I:C-triggered immune response. To conclude, our study suggests that CecA might be a promising molecule for the development of new immunomodulatory antibiotic-substitutive agents in poultry medicine, however, there is still a lot to clarify regarding its cellular effects.